Acute chest syndrome is associated with single nucleotide polymorphism‐defined beta globin cluster haplotype in children with sickle cell anaemia. (16th August 2013) - Bean, Christopher J.; Boulet, Sheree L.; Yang, Genyan; Payne, Amanda B.; Ghaji, Nafisa; Pyle, Meredith E.; Hooper, W. Craig; Bhatnagar, Pallav; Keefer, Jeffrey; Barron‐Casella, Emily A.; Casella, James F.; DeBaun, Michael R.
Summary: Genetic diversity at the human β‐globin locus has been implicated as a modifier of sickle cell anaemia (SCA) severity. However, haplotypes defined by restriction fragment length polymorphism sites across the β‐globin locus have not been consistently associated with clinical phenotypes. To define the genetic structure at the β‐globin locus more thoroughly, we performed high‐density single nucleotide polymorphism (SNP) mapping in 820 children who were homozygous for the sickle cell mutation (HbSS). Genotyping results revealed very high linkage disequilibrium across a large region spanning the locus control region and the HBB (β‐globin gene) cluster. We identified three predominant haplotypes accounting for 96% of the β S ‐carrying chromosomes in this population that could be distinguished using a minimal set of common SNPs. Consistent with previous studies, fetal haemoglobin level was significantly associated with β S ‐haplotypes. After controlling for covariates, an association was detected between haplotype and rate of hospitalization for acute chest syndrome (ACS) (incidence rate ratio 0·51, 95% confidence interval 0·29–0·89) but not incidence rate of vaso‐occlusive pain or presence of silent cerebral infarct (SCI). Our results suggest that these SNP‐defined β S ‐haplotypes may be associated with ACS, but not pain or SCI in a study population of children with SCA.